MERCURY, CHROMIUM, CADMIUM AND LEAD IN PYGOCENTRUS NATTERERI KNER, 1858 AND PROCHILODUS LINEATUS (VALENCIENNES, 1836) FROM TWO RIVERS OF PANTANAL (MATO GROSSO), BRAZIL - Santos Filho, Francisco Morais dos (2016)
The research was conducted in the Upper Paraguay Basin, Pantanal, Mato Grosso, Brazil. This research aimed to evaluate the total mercury (THg), chromium (Cr), cadmium (Cd), and lead (Pb) concentrations in fish tissue. The Upper Paraguay Basin is target of several anthropogenic aggressions, which directly affects its aquatic ecosystem, like the burning of native vegetation, gold exploration, or even the strong exploitation of fish stocks. A total of 78 individuals of 2 different species (44 Pygocentrus nattereri and 34 Prochilodus lineatus) were caught from the Paraguay and Cuiabá rivers. To quantify the THg concentrations it was used an atomic absorption spectrophotometer, Perkin Elmer (FIMS- system), while the readings of Cr, Cd and Pb were performed on an atomic absorption spectrophotometer (AAS-F). The analyzed samples of P. nattereri showed THg concentrations in the muscle between 0.999 and 0.597μg.g-1; and above 0.50μg.g-1, the maximum tolerance concentration recommended for consumption by the World Health Organization; and 43.18% presented concentrations between 0.20 and 0.50μg.g-1. The results for Cr have revealed that 95.45% of P. nattereri and 97.05% of P. lineatus present Cr concentrations above the limits established by the legislation. Cd and Pb concentrations in the muscles of the fish collected showed values under the upper limit for the Brazilian legislation.